ANALYSIS AND DESIGN OF INTEGRATED ONE DOOR SERVICE IN THE MINISTRY OF RELIGIOUS AFFAIRS, KUTAI TIMUR - Bustomi, Tommy; Yulsilviana, Ekawati; Jaelani, Jan Jan (JURNAL IT, 2019)
The One Door Integrated Service Application is a service delivery for several types of services that are organized in an integrated manner in one place and controlled by a management control system. In this application there are two types of services namely customer service (Cs) and front office (FO), in both types of services have different service functions CS functions to provide services to the public and employees who want to do consultations include, Hajj and Umrah services , Marriage, Endowments, Zakat, Promotion, Staffing while FO Providing services to the community in the form of requests to transfer schools, legalizing certificates, mosque recommendations, passport recommendations, Requests for Qibla direction, requests for prayer, requests for clergy, Requests for place of worship data, Requests for marriage data. The application was developed using the Prototype system development method, data collection methods by interviewing, observing and studying literature, analyzing system design using UML (Unifield Modeling Language). In building applications information is used in the PHP programming language, MySQL Database, Apache Local Web Server, Adobe Dreamweaver CS6 as a web editor, and Adobe Photoshop as an image editor. Testing methods The information application uses the Blackbox testing method and Beta testing. The results of this study is that with this web-based application it will facilitate office staff in archiving services to record history and make it easier to serve the general public as well as providing convenience to the community when it will perform services